2017
DOI: 10.1016/j.psychres.2017.01.049
|View full text |Cite
|
Sign up to set email alerts
|

Are people with schizophrenia adherent to diabetes medication? A comparative meta-analysis

Abstract: . Are people with schizophrenia adherent to diabetes medication? A comparative meta-analysis. Psychiatry Research, 250,[17][18][19][20][21][22][23][24] https://doi.org/10.1016/j.psychres.2017.01.049Citing this paper Please note that where the full-text provided on King's Research Portal is the Author Accepted Manuscript or Post-Print version this may differ from the final Published version. If citing, it is advised that you check and use the publisher's definitive version for pagination, volume/issue, and date… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 35 publications
1
11
0
1
Order By: Relevance
“…127 Furthermore, recent data have shown that people with schizophrenia are equally adherent to diabetes medication as the general population, thus further supporting the need for healthcare providers to remain optimistic about prescribing cardiometabolic medications in people with mental illness. 128 Finally, access may be compromised by financial costs, fragmentation of care and stigma. 124,126,129 Although health care should be the one sector where challenging behaviour might be recognized as a symptom of illness, there is evidence that various healthcare providers have stigmatised views on people with mental illness.…”
Section: Looking Beyond Lifestyle: Health Provider and System-level Fmentioning
confidence: 99%
“…127 Furthermore, recent data have shown that people with schizophrenia are equally adherent to diabetes medication as the general population, thus further supporting the need for healthcare providers to remain optimistic about prescribing cardiometabolic medications in people with mental illness. 128 Finally, access may be compromised by financial costs, fragmentation of care and stigma. 124,126,129 Although health care should be the one sector where challenging behaviour might be recognized as a symptom of illness, there is evidence that various healthcare providers have stigmatised views on people with mental illness.…”
Section: Looking Beyond Lifestyle: Health Provider and System-level Fmentioning
confidence: 99%
“…Second, only 4 studies with 144 patients were included; thus, the findings are still preliminary. Third, cognitive deficits are closely associated with metabolic syndrome [26] and non-insulin-dependent diabetes mellitus [31], which are prevalent in a sizeable proportion of patients with severe mental illness [32,33]. All the RCTs included only physically healthy patients, which limits the generalization of the findings in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…Trial data in relation to the use of antidiabetic medications (except for metformin) in services. Meta-analysis has shown that 56% of people with schizophrenia (n=33680) are "adherent" to diabetes medication, which was significantly higher than those without schizophrenia, indicating that diabetic medication programs can be successfully implemented in this population [58]. We believe that future clinical trials that investigate treatment efficacy and switching strategies in T2DM patients in SMI will increase our knowledge, familiarity and confidence in using these agents and lead to increased treatment implementation for T2DM in this population.…”
Section: Five-year Viewmentioning
confidence: 96%
“…We will focus on pharmacological treatments used to manage T2DM in the general population, most of which have little trial exposure in SMI populations. Support for this approach is emphasized in a recent meta-analysis of 10 studies reporting data from 33,910 people with schizophrenia and T2DM which found that people with schizophrenia adhered to diabetic medication on 77.3% of days prescribed (n=32080, 95%CI=73.6-81%, I 2 =99.2%,), and adhered on 4.6% more days per year than those without schizophrenia (p<0.01, 95%CI=2.4-6.7%, I 2 =92.5%, schizophrenia n=19367, controls=170,853) [58].…”
Section: Pharmacotherapy For T2dm In Smimentioning
confidence: 99%